2019
DOI: 10.1111/apha.13324
|View full text |Cite
|
Sign up to set email alerts
|

Keeping heart homeostasis in check through the balance of iron metabolism

Abstract: Highly active cardiomyocytes need iron for their metabolic activity. In physiological conditions, iron turnover is a delicate process which is dependent on global iron supply and local autonomous regulatory mechanisms. Though less is known about the autonomous regulatory mechanisms, data suggest that these mechanisms can preserve cellular iron turnover even in the presence of systemic iron disturbance.Therefore, activity of local iron protein machinery and its relationship with global iron metabolism is import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 165 publications
(346 reference statements)
0
33
0
Order By: Relevance
“…The data obtained showed that the non-polar extracts had ferric chelating activity (Figure 1A). Ferrous turnover is an important process in patients with thalassemia, cardiac disorders, and neurodegenerative diseases; thus, detection of ferric chelating activity in the extracts was a significant finding [41]. Moreover, M. zehntneri polar extracts (EE, ME, FWE, and WE) had superoxide radical-, hydroxyl radical-, and DPPH-scavenging activities, (Figure 1B–D).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data obtained showed that the non-polar extracts had ferric chelating activity (Figure 1A). Ferrous turnover is an important process in patients with thalassemia, cardiac disorders, and neurodegenerative diseases; thus, detection of ferric chelating activity in the extracts was a significant finding [41]. Moreover, M. zehntneri polar extracts (EE, ME, FWE, and WE) had superoxide radical-, hydroxyl radical-, and DPPH-scavenging activities, (Figure 1B–D).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that antioxidant activity may be associated with polyphenols, flavonoids, and polysaccharides [20,40,41,43]. Thus, our findings showed that M. zehntneri extracts, similar to other cactus extracts, exerted their activity in three stages: initiation (DPPH-scavenging activity, shown by all extracts), propagation (ferrous-chelating activity, shown by the non-polar extracts HE and CE), and termination (superoxide and hydroxyl radical-scavenging activity, shown by the polar extracts EE, ME, FWE, and WE) [31,44].…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria are known for their key role in energy production. However, it is less recognized that they also play an important role in iron metabolism [ 55 , 56 , 57 ] and in the modulation of cardiac damage during ischemia and reperfusion [ 58 ]. In fact, the mitochondrion is the sole site of heme synthesis and a major generator of iron sulfur clusters (ISCs), both of which are present in mitochondria and cytosol.…”
Section: Cellular Iron Homeostasis In the Heartmentioning
confidence: 99%
“…The mitochondrion, known as an essential organelle for systemic energy metabolism, confers an important impact on iron homeostasis and modulation of myocardial damage during IRI ( Richardson et al, 2010 ; Lesnefsky et al, 2017 ; Vela, 2020 ). It has been documented that mitochondria provide available sites for heme synthesis and iron–sulfur cluster (ISC) generation, with formation of heme and ISC proteins to be integrated in the mitochondrial oxidative phosphorylation system, which supplies a physiological necessity of cardiac activity for continuous energy through catalyzing electron transport of oxidative iron ( Paul et al, 2017 ).…”
Section: Iron Homeostasis and Its Role In Cardiomyocytesmentioning
confidence: 99%